Implementación de la contabilidad comercial por el sistema de inventario permanente para abarrotes Rocio del cantón La Joya De Los Sachas, provincia de Orellana periodo mayo a julio del 2013 - Lomas Angamarca, Sonia Margoth (2014)
This thesis entitled "IMPLEMENTATION OF BUSINESS ACCOUNTING INVENTORY SYSTEM FOR STANDING SPRAY ABARROTES CANTON JEWEL OF SACHAS, Orellana Province PERIOD MAY TO JULY 2013", I realized that is a prerequisite for obtaining Engineering degree in Accounting and Auditing, CPA. Its development will get input on the economic, social and academic field through the financial results generated during the study period, the same that will tell the owner adopt strategies and policies to decision making for achieving business objectives. By implementing business accounts were complied with the resolution of the objectives, plan and manual accounts according to business needs was developed; was making physical inventory of merchandise noting the products available for sale, according to the interview it was found assets and liabilities held by the company, for the completion of its initial situation and know their heritage, he refused proceeded to order the company documentation and Daybook, once completed became the majorization, Worksheet and culminated in the financial statements as are established: the Income Statement, Balance Sheet and Cash Flow Statement cash. With the results obtained it is concluded that commercial accounting is important in the daily activities of the company since its application allows to obtain real results that will help the owner to improve the economic performance of your business, so that your application for future recommended business.